“ANALYLIS OF ACTION BASED LEARNING FOR TEACHING ENGLISH IN RIOBAMBA HIGH SCHOOL, FOURTH GRADE OF EDUCACIÓN GENERAL BASICA PARALLEL “A” IN THE CITY OF RIOBAMBA. CHIMBORAZO PROVINCE IN THE ACADEMIC YEAR 2018-2019.” - Tualombo López, Karina Elizabeth (2019)
The present research analyzes how English has become the principal language around the world. However according to standards in some countries English level is low. Furthermore, a previously observation did in the pre-professional practices the researcher could observe that students did not have a freely participation in class, they did not have any interest to learn. Moreover, nowadays teachers apply this method that motivates students to learn. For this reason, the principal objective is to analyze how Action Based Learning Method contributes to teaching English at the fourth grade of Educación General Básica parallel “A” at “Riobamba” high school. The method this research applies is a qualitative approach. The level of research was exploratory. The method used was ethnographic. The technique used was the observation and the instrument applied was the checklist. The population consisted of 38 students, 18 girls and 20 boys. The results of this research show that students tried to practice the new vocabulary through the implementation of activities that include movement. Through these activities based on Action Based Learning method helps to enhance the students’ participation during the development of English class. Moreover, students presented good attitudes and enthusiasm because of the application of this method. Action Based Learning Method helps to catch the students’ attention; students show more interest to participate in classes. In conclusion, this method is very beneficial in the English teaching- Learning process because students can perform the tasks in a better way.